Formulation and Characterization of Piroxicam as Self-Nano Emulsifying Drug Delivery System - Fahad F. Salim; Nawal A. Rajab (Iraqi Journal of Pharmaceutical Sciences, 2020)
Piroxicam (PIR) is a nonsteroidal anti-inflammatory drug of oxicam category, used in gout, arthritis, as well as other inflammatory conditions (topically and orally). PIR is practically insoluble in water, therefore the aim is prepare and evaluate piroxicam as liquid self-nanoemulsifying drug delivery system to enhance its dispersibility and stability. The Dispersibilty and Stability study have been conducted in Oil, Surfactant and Co-surfactant for choosing the best materials to dissolve piroxicam. The pseudo ternary phase diagrams have been set at 1:1, 2:1, 3:1 as well as 4:1 ratio of surfactants and co-surfactants, also there are 4 formulations were prepared by using various concentrations of transcutol HP, cremophore EL and triacetin oil. All the constructed prepared formulas have been assessed for in vitro drug dissolution, thermodynamic stability, polydispersity index, robustness to dilution, particle size distribution, drug content, and the dispersibility and emulsification time.From the presented research concluded that the self-nanoemulsifying drug delivery system is the convenient method for improving Dispersibilty and Stability of piroxicam.